Motives For The Migration Of Iraqi Scientific Competencies And Their Implications For Iraqi Society - Mohammed Abdulhussein, Helen (Opción, 2019)
It has become clear today that, in light of globalization and global integration, societies are looking towards a new type of force, after military power has begun to diminish its importance as a basic parameter in measuring the strength and progress of the state, and the world is turning to a new type of power that lies in the cumulative cognitive strength, as it grows The status of knowledge industry and its importance as the main pillar in building modern economies, and strengthens the power of knowledge activities to occupy the most sensitive and influential joints in the community production system, so knowledge is considered the most important manifestation of power in the world of tomorrow, because of its active and influential role in the numbers of human capital and good Stvadh him in the overall development process that looks a state, if I am a human mental abilities and his observations out of de- velopment and its tool, as is the ultimate goal and purpose. Most countries at the present time are competing for investment in the field of scientific minds and competencies and the enticement of those engaged in scientific research from specialized scientists and technicians after realizing that the process of generating value comes through scientific competencies, as it represents the optimal investment in the short and long term, as the experiences of the coun- tries from which it was launched proved early in development Investing in human and cognitive capital is the best option for embarking on the process of development and construction on the one hand, and paving the way for steady steps towards the future on the other hand, especially since trained and qualified scientific competencies are crucial and important in the process of progress and slavery Because it is important for the progress of any nation and drawing its various features, as it constitutes a vital aspect of the various aspects of economic, social and cultural development, and the well-being of the industrialized and civilized countries is appreciated by the scholars and owners of scientific competencies and distinct energies this side, and the extent of their contribution in providing what It is better for humanity through scientific innovations and inventions to supplement the fountains of knowledge on the other hand.